Overcoming Barriers to Electric Freight Vehicle Adoption: A Narrative Review of Global Evidence - Hariri, Ahmad; Zulkarnain , Ahnis (Indonesian Scientific Publication, 2024)
The rapid growth of urban logistics has intensified concerns about sustainability, making Electric Freight Vehicles (EFVs) a critical innovation for reducing greenhouse gas emissions and improving urban air quality. This study aims to provide a narrative review of the factors influencing EFV adoption, with a focus on technological, economic, infrastructural, and policy dimensions. Literature was systematically retrieved from major databases, including Scopus, Web of Science, IEEE Xplore, and Google Scholar, using targeted keywords related to EFVs, sustainable logistics, charging infrastructure, and adoption policies. Inclusion criteria emphasized empirical studies, case analyses, and decision-making frameworks relevant to urban freight logistics. Findings reveal that technological barriers, particularly limited battery range and insufficient charging networks, remain significant impediments to EFV adoption. Economic considerations, such as high initial investment and retrofitting costs, continue to deter smaller logistics firms, although long-term savings in energy and maintenance strengthen the economic rationale. Policy measures, including subsidies, tax incentives, and Low Emission Zones, have proven effective in accelerating adoption, particularly when aligned with infrastructure development. Cross-country comparisons demonstrate uneven progress, with Norway, the Netherlands, and China leading, while many developing regions lag due to systemic and financial constraints. The discussion emphasizes the need for holistic strategies that integrate policy, infrastructure, and technological innovations. Future research should explore longitudinal policy impacts, innovative charging solutions, and behavioral aspects of adoption to inform more effective pathways toward sustainable urban logistics.